Calcitonin Gene-Related Peptide, Vascular Endothelial Growth Factor, and Clinical Manifestations in Women With Fibromyalgia. Issue 1 (6th January 2023) - Rus, Alma; López-Sánchez, José Alberto; García-Ríos, María Carmen; Tapia-Haro, Rosa María; Casas-Barragán, Antonio; Correa-Rodríguez, María; Aguilar-Ferrándiz, María Encarnación
Abstract : Background: Fibromyalgia is a complex illness to diagnose and treat, which significantly impairs patients' quality of life. Objectives: The study aims were to compare levels of calcitonin gene-related peptide and vascular endothelial growth factor between patients with fibromyalgia and healthy controls and to examine their relationship with the main clinical manifestations of fibromyalgia. Methods: This case–control study included 42 women diagnosed with fibromyalgia and 22 healthy women. Serum calcitonin gene-related peptide and vascular endothelial growth factor levels were spectrophotometrically analyzed by enzyme-linked immunosorbent assay. Clinical manifestations were assessed by means of self-administered questionnaires, including functional capacity in daily living activities, musculoskeletal pain, fatigue, anxiety, and sleep quality. The predictive value of these parameters in fibromyalgia was determined by receiver operating characteristic curve analysis. Results: Serum calcitonin gene-related peptide levels significantly increased in the fibromyalgia group in comparison to the control group. However, there were no significant differences in vascular endothelial growth factor levels between patients and controls. No significant correlations were found between calcitonin gene-related peptide and vascular endothelial growth factor and the symptoms analyzed. Discussion: Serum calcitonin gene-related peptide levels were dysregulated in women with fibromyalgia and may be a reliable parameter to help diagnose this complex syndrome.